The effect of gemargatara gymnastics training on increasing students' vo2max abilities - Imansyah, Yadi; Azhar Fikri, Lalu Muhammad; Anam, Khaerul (Jurnal Porkes, 2023)
Gemargartra gymnastics is a new exercise combined with traditional game movements. The aim of this research is to determine the effect of gemargatra gymnastics on V02max. The problem in this research is that the heart and lung capacity has not been measured when doing gemargatra exercises. The method of this research is experimental tests and measurements by giving treatment 01. The population in this study was grade 11 with a total of 35 people. The instrument in this research uses the bleep test and the data analysis technique uses the sample dependent t test through the requirements test. Based on data analysis in this study using the t test, these results were proven by a comparison of the average calculation results in the pretest and posttest t test groups (32.8 < 37.6) t count 17.78 > t table 2.13. And there was an increase in ability results between the pretest and posttest of 1.40, which means that the application of gemargatra exercises had an effect on increasing Vo2max. It was concluded that aerobic exercise can have an influence on body composition because when you train, the body will respond and if the exercise is done continuously, the body will adapt. gemargatra exercise can have a significant influence on increasing VO2Max abilities